1994
DOI: 10.1557/s0883769400047722
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Vapor Deposition of Copper for IC Metallization: Precursor Chemistry and Molecular Structure

Abstract: In the microelectronics industry, integrated circuit (IC) device performance is continually increasing while the critical feature sizes are rapidly decreasing. Since this trend is expected to continue for future generations of ICs, areal density constraints often require that circuit designs utilize multilevel structures with vertical interconnects. It was recently demonstrated that the resistivity of the metal interconnects may limit device performance in multilevel thin-film structures. Although Al metallurg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 67 publications
1
33
2
Order By: Relevance
“…Gravimetry of the sample indicated that the density of the film (in the range 8.5 ± 0.5 g cm ±3 ) was comparable to that of metallic Cu (r = Once the first 0.5 mm copper layer had been deposited by CVD, classical electroless or electrodeposition procedures allowed thicker deposition (50± 100 mm) in a short time (less than 1 h). The resistivity of the copper films that was measured on 0.5 mm thick films was r = 1.9 ± 0.2 mW cm; this value was comparable to what is generally observed with CVD-deposited films (1.8 mW cm), [4,5] and to the bulk Cu value (1.67 mW cm). Figure 4 shows XPS spectra of a Cu sample before ( Fig.…”
Section: Metallization Of the Activated Teflon Surfacesupporting
confidence: 83%
See 2 more Smart Citations
“…Gravimetry of the sample indicated that the density of the film (in the range 8.5 ± 0.5 g cm ±3 ) was comparable to that of metallic Cu (r = Once the first 0.5 mm copper layer had been deposited by CVD, classical electroless or electrodeposition procedures allowed thicker deposition (50± 100 mm) in a short time (less than 1 h). The resistivity of the copper films that was measured on 0.5 mm thick films was r = 1.9 ± 0.2 mW cm; this value was comparable to what is generally observed with CVD-deposited films (1.8 mW cm), [4,5] and to the bulk Cu value (1.67 mW cm). Figure 4 shows XPS spectra of a Cu sample before ( Fig.…”
Section: Metallization Of the Activated Teflon Surfacesupporting
confidence: 83%
“…Film resistivities between 1.8 and 2.5 mW cm, as opposed to 1.67 mW cm for bulk copper, have been reported. [4,5] In this work, two different precursors were used to check if the phenomenon we observed was precursor dependent: (VTMS)Cu(hfac) and (MHY)Cu(hfac) (where VTMS = vinyltrimethylsilane and MHY = 2-methyl-1-hexene-3-yne). The temperature of the source and the reactor sample plate were slightly dependent on the precursor: 45 C (source)/ 210 C (sample plate) for (VTMS)Cu(hfac) and 65 C (source)/240 C (sample plate) for (MHY)Cu(hfac).…”
Section: Metallization Of the Activated Teflon Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of these precursors and CVD processes using such precursors has been reviewed recently.72. 73 The Cul+ (I) precursors are generally available in liquid form, making their delivery into the CVD reactor easy. They decompose on heating through a disproportionation reaction, 2L Cu(I)(P -diketonate) (13) + Cu(0) + Cu(II)(P -diketonate), + 2L leading to a neutral copper atom that deposits on the substrate and a Cu (11) metal-organic compound that is pumped out.…”
Section: B Chemical Vapor Depositionmentioning
confidence: 99%
“…Other compounds of the same family have demonstrated valuable results [7,24,25]. Within this family of copper(I) CVD precursors, the physical properties can easily be varied by structural modifications, i.e.…”
Section: Introductionmentioning
confidence: 99%